The pain on the political battlefield—structuring the role of the media in protests triggered by mass murders in Serbia - Jevtić, Milica (Frontiers in Political Science, 2025)
In May 2023, Serbia witnessed two unprecedented crimes. First, a 13-year-old boy killed nine of his classmates and a school security guard in central Belgrade. The following day, in what appeared to be a copycat act, a 12-year-old man randomly shot and killed nine young people and seriously injured 12 others. These tragedies triggered a wave of protests, initially sparked by shock and grief, but which soon took on a political dimension, accompanied by a set of media-related demands and calls for the resignation of government officials. This paper seeks to explore how media frames were constructed during the protests that followed these tragedies, from early May until November, when snap parliamentary elections were announced. The analysis focuses on seven frames employed by the pro-government tabloid Informer and the opposition-leaning newspaper Danas, each of which shaped the portrayal of the protests in accordance with their respective political alignments-within the context of Serbia’s deeply polarized media, political, and social landscape. Findings indicate that the media played a significant role in the emergence, maintenance, and eventual dissolution of the protests. Both newspapers actively shaped the character of the protests and the portrayal of protest participants in ways deemed suitable for their readerships—that is, for voters aligned with either side of the media-political divide. Both outlets relied heavily on conflict framing; however, Informer also prominently featured a national security threat frame. Additionally, a morality frame was present in both newspapers, though approached from entirely different perspectives.